Robust methods for estimating functional connectivity - Nagarajan, S.S.; Owen, J.P.; Hinkley, L.B.; Attias, H.T.; Sekihara, K. (NeuroImage (Orlando, Fla.), 2009)
Noninvasive imaging of functional connectivity refers to statistical inferences about causal interactions in activity across different brain regions observed during rest or while a subject is performing a task. Application of coherence to noisy functional imaging data, like fMRI, with limited number of samples can be quite unreliable. [...]inferring functional connectivity using bivariate methods that neglect the influence of voxels not under consideration can give inconsistent results.